Immigrant Japan : mobility and belonging in an ethno-nationalist society - Liu-Farrer, Gracia (Cornell University Press, 2020)
"Describes how millions of immigrants make their lives in Japan, highlighting the tensions between belonging and not belonging in this ethno-nationalist immigrant country"--